The Legal Position of Children of Incest (A Study of Madhhab Scholars and Compilation of Islamic Law) - Djawas, Mursyid; Achyar, Gamal; Bustanul Arifin, Nursyirwan; Reza, Masri; Umar Yakub, Baharuddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This study aims to discuss the legal position of children of incest, the opinions of madhhab scholars, and the provisions on inheritance rights of children of incest according to Islamic law. This normative legal study used the Islamic law methodological approach (ushul fiqh) and the legislation/ statute approach. The data were obtained through a literature review of the laws or legal rules. The results of the study revealed that the legal position of children of incest in Islamic law is in terms of civil matters (i.e., lineage/blood relations) between the children and the parents. The children only establish lineage ties with their mothers and their maternal families. Further, the madhhab scholars Imam Malik and Imam Shafi’i argue that adultery does not produce legal descendants, and therefore, the children are not related to the male adulterer but to the female, as they are born from an illegitimate relationship. In addition, Imam Hanafi and Imam Hanbali state that it is forbidden for a man to marry the daughter born of his adultery, as she is equal to his legitimate daughter. This is the view of the majority of madhhab scholars. In the case of the inheritance rights of children of incest, the children can only get an inheritance from their mothers and the maternal families, apart from the lineage, guardianship, inheritance, and livelihood rights. However, al-Jaziri, a contemporary scholar, views that children of incest are still legitimate children whose lineage and inheritance are still related to both father and mother.